The Effect of Organizational Ethical Climate on Perceived Power Distance: A Research on Nurses - Aysel Arslan; Hasan Gül (Association of Nurse Managers, 2022)
Aim: This research aims to determine the effect of nurses' perceptions of organizational ethical climate on their perceptions of power distance. Method: For the research, the data collected from 257 nurses working in a public institution by a survey method were analyzed in the SPSS software. The questionnaire used in the study is composed of the 'Organizational Ethics Climate Scale', 'Organizational Power Distance Scale' with sociodemographic questions. The data were analyzed using descriptive statistical methods, and correlation and regression analysis. Results: One-way ANOVA analysis was performed to determine whether the nurses' perceptions of organizational ethical climate and organizational power distance show a significant difference according to the age, level of education, and professional seniority of nurses. As a result of the analysis, while only the perception of organizational power distance did not differ significantly according to the education level variable (p > 0.05); a significant difference was found in all other variables (p < 0.05). The mean total score of the 'Organizational Ethics Climate Scale' was 3.68 and the mean total score of the 'Organizational Power Distance Scale' was 2.65. There was no correlation between nurses' perceptions of organizational ethical climate and organizational power distance. According to the regression analysis, nurses' perceptions of organizational ethical climate do not affect their perception of organizational power distance, which is the dependent variable (F = 2.366; R = 0.096; R² = 0.009; p = 0.125). Conclusion: As a result of the analyses, it was concluded that nurses' perception of organizational ethical climate did not have a significant effect on their perception of power distance.